(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
After having recalled the different forms of legal innovation and the function that the doctrine plays in fostering such innovation, the essay will focus on the emergence, in Italy, of the “biodiritto” label, on its ordering function as a category and on the role of doctrine as an engine of its evolution.